Pengaruh Budaya Organisasi, Kepuasan Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai: Studi Pada BPJS Kesehatan Kantor Cabang Banjar - Andi Andriyana (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
Starting from the existence of several problems faced, namely there is a decrease in the quality of work as evidenced by the overall table of the national fluid index from 2020-2022. There is a decrease in the quantity of work based on the overall table of the National Achievement Index from 2020-2022. Improper timeliness in service time for participants has become an indicator of the decline in the overall value of the National Index of achievements from 2020-2022. Work effectiveness has decreased due to the fact that there are still vacant positions in the organizational structure, forcing employees to handle other work. Lack of employee independence, so that performance does not develop if there is no supervisor. The culture of BPJS Kesehatan is dynamic so that during the transition period employees experience difficulties. There are vacant positions in the organizational structure, so some employees do double jobs to keep the program running. Leaders do not understand the potential of each employee and tend to always rely on employees who have done this side job. The method used is descriptive quantitative. the results of research on Organizational Culture have a positive and significant effect on Employee Performance. This means that if the organizational culture increases, the employee's performance also increases. Job Satisfaction has a positive and significant effect on Employee Performance. This means that if job satisfaction increases, employee performance also increases. Leadership style has a positive and significant effect on employee performance. This means that if the leadership style increases, the employee's performance also increases. Organizational culture, job satisfaction and leadership style have a positive and significant effect on employee performance. This means that if organizational culture, job satisfaction and leadership style increase, employee performance also increases.